Utilização de Daphnia sp. alimentada com Haematococcus pluvialis e Chlorella vulgaris no cultivo berçário do camarão Litopenaeus vannamei em sistema de bioflocos - CAMPOS, Clarissa Vilela Figueiredo da Silva (2022)
Management for the reuse of aquaculture effluents have been prioritized in order to achieve sustainable aquaculture. The use of aquaculture effluents for the production of live food can be a promising alternative. Within this scenario, this study evaluated the use of effluent from the cultivation of Nile tilapia in a biofloc system for the production of the water flea Daphnia similis and D. magna from two experimental moments: 1) Use of effluent treatment (sedimentation and no-sedimentation) combined with different salinities (1, 2, 3 and 4) in the cultivation of D. similis; and 2) Influence of autotrophic (without effluent) and mixotrophic (with effluent) culture system combined with different microalgae diets: Chlorella vulgaris and Haematococcus pluvialis (cystic and vegetative phase) on the growth and nutritional composition of D. magna. In the first experiment, it was reported that no-sedimentation of effluent combined with salinity 3 had the best growth of water flea, while the sedimentation of effluent in salinity 2 had better bioremediation from the reduction of nitrogen compounds and orthophosphate. In the second experimental moment, the mixotrophic system using C. vulgaris as feed had better results of growth and increase of lipids and protein for D. magna. The cultures with H pluvialis in cystic phase as feed reported best reduction of nitrogen componds and orthophosphate, despite it had not achieved success on water flea growth, there was death of 100% of population of individuals on day 4 of cultivation. In this way, the findings of this research contribute to the management of production of live food for aquaculture and biorremediation of these wastewater promoting a better sustainable aquaculture for productive sector and new possibilities for alternative protein sources.